Optimization of the wireless intercom system for overhead covered depots for electric trains and design of digital-analog compatible relays - WANG Weili (Dianxin kexue)
In environments where the overhead covered depots for electric trains employs multi-density structural columns, wireless intercom personnel can only communicate at close range, making it impossible to conduct wireless intercom while moving within a large area of the facility. In response to the requirements of the wireless intercom system for overhead covered depots for electric trains, the existing equipment of first-ever Depot for Electric Trains was optimized, proposing for the first time in railway communications a relay solution for a digital/analog compatible wireless intercom system. Simultaneously, self-excited interference elimination was realized and a set of system equipment suitable for railway depots for electric trains was innovated, enabling the system to meet the demand for direct intercom communication among personnel across the entire ultra-large area. Field tests verify the design level and application effectiveness of this system, reducing the system's bit error rate to below 1% while satisfying business needs. This provides references for the design of wireless communication systems in similar environments, such as passenger and freight train stations, logistics parks, ports, and other scenarios.